2018
DOI: 10.1186/s12913-018-3454-6
|View full text |Cite
|
Sign up to set email alerts
|

Pay for performance program reduces treatment needed diabetic retinopathy - a nationwide matched cohort study in Taiwan

Abstract: BackgroundPay-for-Performance programs have shown improvement in indicators monitoring adequacy and target achievement in diabetic care. However, less is known regarding the impact of this program on the occurrence and long-term effects of diabetic retinopathy. The objective of this study was to determine the effect of pay-for-performance program on the development of treatment needed for diabetic retinopathy in type 2 diabetes patients.MethodsWe conducted a nationwide retrospective cohort study with a matchin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…But the report showed a low adherence to follow-up appointments in a public clinic with low cost and high accessibility in USA 13 . In Taiwan, National Health Insurance offers low cost and high accessibility of eye care compared to the rest of the world, but the regular follow-up rate is still low 14 . Compared to age-related macular degeneration (AMD), diabetic macular edema (DME) patients have worse compliance and adherence to treatment.…”
Section: Discussionmentioning
confidence: 99%
“…But the report showed a low adherence to follow-up appointments in a public clinic with low cost and high accessibility in USA 13 . In Taiwan, National Health Insurance offers low cost and high accessibility of eye care compared to the rest of the world, but the regular follow-up rate is still low 14 . Compared to age-related macular degeneration (AMD), diabetic macular edema (DME) patients have worse compliance and adherence to treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the patients maintaining a good relationship with their healthcare provider(s), as shown by higher COC values, and those undergoing regular kidney or CV tests, also experienced a lower risk of retinopathy. A previous study similarly reported that participation in a P4P program improved the care of patients with diabetes through teamwork, provided they followed the clinical guidelines under the payment scheme 38 . Furthermore, chronic diseases require long-term care, and patients with type 2 diabetes benefit from a stable physician-patient relationship (in the high COC group) based on trust or from an integrated care team that can collaborate with other professionals to provide treatment in certain areas, such as dietary guidance and exercise coaching.…”
Section: Discussionmentioning
confidence: 99%
“…Diabetes mellitus (DM) is a prevalent disease with significant comorbidities that not only affect the eyes but also cause cardiovascular disease, nephropathy, and neuropathy. Diabetic retinopathy (DR) affects an estimated one in three people with DM and may result in severe visual impairment [1]. Diabetic macular edema (DME), a common complication of DR, is pathologically linked to the disruption of the blood-retinal barrier [2].…”
Section: Introductionmentioning
confidence: 99%